The community in rural America - Wilkinson, Kenneth P., author; University Press of Colorado, publisher (Colorado State University. Libraries, 2023)
This revised edition of The Community in Rural America, by Kenneth P. Wilkinson presents Wilkinson's ground-breaking work in its original form and contains a new foreword aimed at clarifying several key concepts in interactional theory.--Provided by publisher.
Keywords: Rural development -- United States; Sociology, Rural; Communities; Community life; United States -- Rural conditions